Exploring Red, Green, and Blue Light‐Activated Degradation of Perovskite Films and Solar Cells for Near Space Applications. Issue 3 (6th March 2020) - Xiao, Wei; Yang, Jianming; Xiong, Shaobing; Li, Danqin; Li, Yanqing; Tang, Jianxin; Duan, Chungang; Bao, Qinye
Abstract : RGB Light Absorption In article number 1900394, Qinye Bao and co‐workers investigate the effect of red, green, and blue (RGB) light illumination on the stability of perovskite films and photovoltaic devices in the medium vacuum that belongs to near space. The perovskites exhibit different degradations, which is attributed to the strong coupling between photoexcited carriers and crystal lattice, and the diversity of RGB light absorption in the perovskites.